(001)-oriented Cu2-ySe thin films with tunable thermoelectric performances grown by pulsed laser deposition. Issue 6 (July 2015) - Lv, Yanhong; Chen, Jikun; Zheng, Ren-Kui; Shi, Xun; Song, Junqiang; Zhang, Tiansong; Li, Xiaomin; Chen, Lidong
Abstract: Highly (001)-oriented Cu2- y Se thin films with tunable thermoelectric performances have been grown by pulsed laser deposition. By using targets with different Cu/Se ratios that further determines the copper deficiency of as-grown films, the carrier concentrations of as-grown films are tuned within a broad range from 10 18 to 10 21 cm −3 . The optimum performance is observed at carrier concentration 1.58×10 20 cm −3 . The distinct properties of Cu2- y Se thin films with nearly ideal chemical stoichiometric ratio are observed. In addition, a weak change in the electrical transport during the second-order phase transition was observed in the thin films due to the anisotropic structure of the Cu2- y Se.